2000
DOI: 10.1002/mpr.75
|View full text |Cite
|
Sign up to set email alerts
|

Expressed Emotion about children: reliability and validity of a Camberwell Family Interview for Childhood (CFI‐C)

Abstract: A Camberwell Family Interview for Childhood (CFI-C) was developed by adding questions about the family impact of the child's problems to a semi-structured interview on child psychiatric symptoms. The whole CFI-C took under an hour to administer; the questions about family impact added 15-20 minutes. The inter-rater reliability was good (kappa 0.64-1.0). Mothers of 25 boys aged four to nine years referred with disruptive behaviour, and 25 matched controls were interviewed twice in five months. Test-retest stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…18 Child maltreatment, domestic violence, and low maternal warmth are associated with childhood depression and anxiety. 19,20 Thus, children's individual characteristics may be further confounding variables that could explain the relation between socioenvironmental factors and children's likelihood of being involved in bullying.…”
mentioning
confidence: 99%
“…18 Child maltreatment, domestic violence, and low maternal warmth are associated with childhood depression and anxiety. 19,20 Thus, children's individual characteristics may be further confounding variables that could explain the relation between socioenvironmental factors and children's likelihood of being involved in bullying.…”
mentioning
confidence: 99%
“…Hodes et al (1999b), for example, in a study of children and adolescents suffering from epilepsy, reported interrater reliabilities (Spearman correlation coefficients) of 0.96 for positive remarks, 0.80 for warmth, 0.94 for critical comments and 0.90 for emotional overinvolvement. The reliabilities reported by Scott and Campbell (2001) were similarly high. The figures in a study of 43 adult post-traumatic stress disorder (PTSD) sufferers by Tarrier et al (1999) were very similar, with a 100% agreement on overall EE status, and correlations of 0.75 for critical comments, of 1.0 for hostility, of 0.97 for warmth, of 0.55 for positive remarks and of 0.95 for EOI.…”
Section: Reliability Of Ee Measurementmentioning
confidence: 80%
“…More recently, Hodes et al (1999a,b) have adapted the CFI for use in studies concerning children; and Scott and Campbell (2001) have produced a shorter version. Other studies with children have employed the Five Minute Speech Sample (FMSS) developed by Magaña et al (1986) as a less time-consuming method of gleaning similar information.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that mothers of children with behavioural and emotional disorders express more critical comments, fewer positive comments, and less warmth to their children than control parents (Scott & Campbell, 2001). As maternal warmth is important for children's competence, behaviour and development (MacDonald, 1992), high levels of maternal warmth may be critical for low birth weight children and may moderate the risk of long-term cognitive and behavioural difficulties (Tully et al, 2004).…”
Section: Strategies For Improvementmentioning
confidence: 98%